Immigrants et travail à Montréal: la dynamique de l'établissement professionnel des dix premières années - Godin, Jean-François (Université de Montréal, 2005)
Keywords: Travail

Le Montreal Council of Women / Conseil des Femmes de Montréal, de 1940 à 1967, à travers les questions de planification urbaine, d'immigration et des femmes dans le monde du travail - Hilairet, Sabine (Université d'Angers, 2003)
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Travail

La migration féminine qualifiée d’origine sud-américaine à Montréal: ressources culturelles et symboliques, et stratégies d’accès au marché de l’emploi - Guillen Castro, Maritza (Université de Montréal, 2009)
Keywords: Femmes; Travail

Expérience migratoire antérieure et déqualification. Étude de cas portant sur des immigrants russophones à Montréal - Vaynman, Irina (Université de Montréal, 2012)
Keywords: Russes; Travail

Les Italo-Montréalais [sic] et leur histoire (1ère partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2019)
Keywords: Italiens; Travail

Le parcours de réorientation professionnelle d’immigrantes hautement qualifiées à Montréal: une étude exploratoire - Germain, Danielle (Université de Montréal, 2013)
Keywords: Famille; Femmes; Travail

De l'exil à la communauté : une histoire de l'immigration haïtienne à Montréal 1960-1990 - Saint Victor, Alain (Université du Québec à Montréal, 2018)
Keywords: Haïtiens; Travail

Edmond Fournier, charpentier-menuisier à Montréal (1876-1946): la petite histoire d'une famille ouvrière sur des cartes postales - Fournier, Louis (Histoire Québec, 2017)
Keywords: Charpentiers; Famille; Menuisiers; Travail

Moving into the World of Work. Youth Today and a Century Ago - Castel, Frédéric; Olson, Sherry (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Enfants; Famille; Mobilité résidentielle; Navettage; Travail

Juifs marocains à Paris et à Montréal - Messika, Martin; Cohen, Yolande (Les sépharades du Québec. Parcours d'exils nord-africains, 2017)
Keywords: Juifs; Maghrébins; Mariage; Marocains; Travail

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Population, Social Identities, and Daily Life - Gauvreau, Danielle (Montreal: The History of A North American City, 2018)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Entrepreneurs in the New Economy: Immigration and Sex Effects in the Montreal Metropolitan Area - Paré, Sylvie; Therasme, Kelogue (Journal of International Entrepreneurship, 2010)
The recent literature on women’s entrepreneurship shows that they are underrepresented in the main stream economy when compared to their male counterparts, a phenomenon typically observed in other urban contexts. Approximately 30% of the entrepreneurs in the Montreal metropolitan area are women, active in a variety of sectors of the general economy. Their underrepresentation is still greater in the new economy, that is, those sectors that are knowledge-based and/or specialized in information technologies and communications. In this article, we examine the place of female entrepreneurs in the larger economy and in the new economy as related to their immigrant and/or ethnic origins. We seek in this paper to establish a comparative analysis of the situation of women entrepreneurs in immigrant-origin groups, focusing our attention on both the presence of women in entrepreneurial positions and the differential impact associated with membership in an immigrant-origin group. Based on data derived from Scott's Directory of 2007, we first determined an operational definition of the new economy and then analyzed the data from the perspective of sex and ethnic/immigrant origin. New economy enterprises represent approximately 12% of businesses in the Montreal metropolitan area, the majority of which are of the knowledge-based variety, and there is a relative, statistically significant absence of women from such enterprises. At the same time, there is a significantly greater presence of women drawn from minority groups, that is, from groups other than the Anglo-Canadian and French-Canadian dominant groups.
Keywords: Femmes; Travail

Le rôle des réseaux dans l'insertion économique d'une cohorte d'immigrants à Montréal - Chavez, Brigitte (Université de Montréal, 2000)
Keywords: Anglophones; Travail

Mapping Work in Early Twentieth-Century Montreal: A Rabbi, a Neighbourhood, and a Community - Poutanen, Mary Anne; Gilliland, Jason (Urban History Review / Revue d'histoire urbaine, 2017)
Keywords: Famille; Juifs; Travail

The Montreal Shtetl: Making Home After the Holocaust - Abramson, Zelda; Lynch, John (Between the Lines, 2019)
Keywords: Famille; Juifs; Travail

"My Love, How Different Life Is Here..." A Young Italian Woman's Impressions of Postwar Montreal - Cancian, Sonia (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Femmes; Italiens; Langue; Travail

L'emploi des femmes judéo-marocaines à leur arrivée à Montréal (1956-1978) - Néméh-Nombré, Philippe (Les sépharades du Québec. Parcours d'exils nord-africains, 2017)
Keywords: Femmes; Juifs; Maghrébins; Marocains; Travail

Agents of Change, Colours of Resistance: The Socio-Economic Integration of Filipina Live-In Caregivers in Montreal - Kapiga, Isabelle (Université Concordia, 2009)
Keywords: Femmes; Philippins

Mad Flight? The Montréal Migration of 1896 to Brazil - Zucchi, John (Journal of Canadian Historical Association / Revue de la Société historique du Canada, 2013)

L'impact de la conjoncture économique sur la situation en emploi d'une cohorte d'immigrants établie à Montréal - Fassi Fihri, Mohamed (Université de Montréal, 2003)

Résidence et liens de parenté des artisans de Montréal en 1741 - Groulx, François; Gauthier, Jean-Richard (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2000)
Keywords: Artisans; Arts sacrés; Famille

L’immigration féminine au Canada durant les années 1920: la mise en place d’une politique fondée sur le "genre" - Vallée, Marie-Hélène (Recherches féministes, 2002)
Keywords: Britanniques; Femmes

Transition of Asylum Seekers from Shelters to Independent Living - Balyejjusa, Moses Senkosi (Université McGill, 2009)

Enquête sur les relations problématiques entre Français et Québécois francophones - Dupuis, Jean-Pierre (Recherches sociographiques, 2012)
Keywords: Francophones; Français

Les trajectoires de l'intégration professionnelle des immigrants iraniens travaillant comme chauffeurs de taxi à Montréal - Namazi, Vahideddin (Université de Montréal, 2010)
Keywords: Iraniens

Main-d'oeuvre immigrante et développement dualiste: l'économie canadienne au milieu du XIXe siècle - Seccareccia, Mario; Saint-Germain, Maurice (Histoire sociale / Social History, 2001)
Keywords: Britanniques

Dynamiques démographiques à Montréal, 1880-1900 - Gauvreau, Danielle; Olson, Sherry; Thornton, Patricia (Le fait urbain, 2020)
Keywords: Britanniques; Femmes; Francophones; Fécondité; Irlandais; Mariage; Mortalité; Protestants; Travail; État civil

Butcher, Baker, Cabinetmaker? A View of Montreal's Scottish Immigrant Community from 1835 to 1865 - McNabb, Heather (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Écossais

Habiter, prendre pied, s'établir. Les commerçants et manufacturiers juifs de Montréal, 1918-1930 - Taschereau, Sylvie (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Juifs